RADIOPROTECTIVE ACTIVITY OF FICUS RACEMOSA ETHANOL EXTRACT AGAINST ELECTRON BEAM INDUCED DNA DAMAGE IN VITRO, IN VIVO AND IN SILICO - K, Vinutha; M, Vidya S; Kumari, Suchetha N; Sanjeev, Ganesh; G, Nagendra H; ., Pradeepa; Rao, Vaman C (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
<!–[if gte mso 9]> <![endif]–> Objective: To investigate the radioprotective effect of Ficus racemosa (Fr) ethanol stem bark extract against electron beam radiation (EBR) induced DNA damage using in vitro, in vivo and in silico models. Methods: The extract of Fr was tested against radiation induced DNA damage by exposing pBR322 plasmid to different EBR dose rates. Comet assay was conducted using mice which were exposed at 6Gy EBR. In silico study was performed by inhibiting p53 protein C-chain (1TUP C) using phyto chemicals of Fr. Results: The in vitro results revealed that, Fr at lower concentration (50Âµg) showed inhibitory effect on radiation induced DNA damage compared with control. Exposure of mice to 6Gy EBR increased comet parameters like TL (Tail length), OTM (Olive tail moment) and %T (percentage of DNA in the tail) of blood lymphocytes. Fr ethanol extract given orally prior to irradiation at a dose of 400 mg/kg body weight protected the DNA from the radiation damage. The phytochemicals of Fr showed clear interaction with p53 protein chain C, specifically binding to Arginine 248 (ARG248) and Arginine 273 (ARG273) amino acid residues thereby inhibiting the p53 protein-DNA interaction upon radiation. Conclusion: The present study indicates that Fr ethanol extract significantly reduced radiation induced DNA damage in vivo and in vitro. It also showed that the biologically active compounds of Fr have ability to inhibit wild p53 protein which is responsible for apoptosis; these compounds can be used as radioprotectors during chemotherapy to protect normal tissues surrounding cancerous tissue. Â <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>